HF Radar Activity in European Coastal Seas: Next Steps toward a Pan-European HF Radar Network - Rubio, Anna; Mader, Julien; Corgnati, Lorenzo; Mantovani, Carlo; Griffa, Annalisa; Novellino, Antonio; Quentin, Céline; Wyatt, Lucy; Schulz-Stellenfleth, Johannes; Horstmann, Jochen; Lorente, Pablo; Zambianchi, Enrico; et al. (Frontiers in Marine Science, 2017)
High Frequency Radar (HFR) is a land-based remote sensing instrument offering a unique insight to coastal ocean variability, by providing synoptic, high frequency and high resolution data at the ocean atmosphere interface. HFRs have become invaluable tools in the field of operational oceanography for measuring surface currents, waves and winds, with direct applications in different sectors and an unprecedented potential for the integrated management of the coastal zone. In Europe, the number of HFR networks has been showing a significant growth over the past 10 years, with over 50 HFRs currently deployed and a number in the planning stage. There is also a growing literature concerning the use of this technology in research and operational oceanography. A big effort is made in Europe toward a coordinated development of coastal HFR technology and its products within the framework of different European and international initiatives. One recent initiative has been to make an up-to-date inventory of the existing HFR operational systems in Europe, describing the characteristics of the systems, their operational products and applications. This paper offers a comprehensive review on the present status of European HFR network, and discusses the next steps toward the integration of HFR platforms as operational components of the European Ocean Observing System, designed to align and integrate Europe's ocean observing capacity for a truly integrated end-to-end observing system for the European coasts.